2014
DOI: 10.3389/fmicb.2014.00675
|View full text |Cite
|
Sign up to set email alerts
|

H-NS is a repressor of major virulence gene loci in Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus, a leading cause of seafood-associated diarrhea and gastroenteritis, harbors three major virulence gene loci T3SS1, Vp-PAI (T3SS1+tdh2) and T6SS2. As showing in this study, the nucleoid-associated DNA-binding regulator H-NS binds to multiple promoter-proximal regions in each of the above three loci to repress their transcription, and moreover H-NS inhibits the cytotoxicitiy, enterotoxicity, hemolytic activity, and mouse lethality of V. parahaemolyticus. H-NS appears to act as a major re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…It has been previously shown that V. parahaemolyticus H-NS acts as a transcriptional repressor of the T3SS1 genes, exsA and exsB (VP1700), through direct protein-DNA association [13]. This study demonstrates that there is a similar mechanism for the repression of exsD by H-NS in V. parahaemolyticus.…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…It has been previously shown that V. parahaemolyticus H-NS acts as a transcriptional repressor of the T3SS1 genes, exsA and exsB (VP1700), through direct protein-DNA association [13]. This study demonstrates that there is a similar mechanism for the repression of exsD by H-NS in V. parahaemolyticus.…”
Section: Introductionmentioning
confidence: 51%
“…The wild-type (WT) V. parahaemolyticus strain RIMD 2210633 and its hns nonpolar mutant (Dhns) have been described previously [13]. Briefly, the 540 and 618 bp DNA regions upstream and downstream of hns were amplified by PCR, purified, and used as templates to create an 1158 bp deletion construct that was subsequently inserted between the Pst I and Sph I sites of pDS132.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations